Становлення системи власних ресурсів Європейського Союзу - Конончук, І.; Kononchuk, I. (СНУ ім. Лесі Українки, 2018)
У статті проаналізовано акти первинного й вторинного права, які регулюють систему власних ресурсів Європейського Союзу (далі – ЄС). Охарактеризовано основні етапи становлення цієї системи. Зазначено, що бюджет ЄС фінансується за рахунок власних ресурсів та інших фінансових надходжень. Рада може запровадити нові категорії власних ресурсів чи скасувати будь-які з наявних. Визначено систему власних ресурсів ЄС як основного елементу дохідної частини бюджету ЄС. Щорічний бюджет ЄС повинен відповідати багаторічному фінансовому рамковому плану, котрий має забезпечувати впорядкований розвиток видатків ЄС у межах його власних ресурсів. The article analyzes the acts of primary and secondary law which govern the system of the European Union own resources. The article describes he main stages of this system formation. The author states that the EU budget is financed from its own resources. The EU Council has the authority to introduce new categories of its own resources or cancel any existing ones. These decisions about on the EU own resources system come into force only after the approval by all member-states in accordance with the constitutional rules of each of the states. The emphasis is laid on the system of the EU own resources as the main revenue source of the EU budget. The budget revenues and expenditures should be balanced. The annual EU budget must meet the long-term financial framework plan. The financial framework has to ensure the orderly development of EU expenditure within its own resources system.
Formation of the European Union Own Resources System
Keywords: бюджет; бюджетний процес; доходи й видатки бюджету; мито; система власних ресурсів ЄС; фінансовий регламент; budget; budget process; budget revenues and expenditures; duty; EU own resources system; financial regulation